Penerapan Metode Demonstrasi Guna Meningkatkan Hasil Belajar Bahasa Inggris di Kelas VIII SMP Negeri 10 Mandau - Junaidi, Junaidi; Sulastri, Leni; Gusnelly, Gusnelly (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
This study aims to describe English language learning in class VIII.a SMP Negeri 10 Mandau on English language mastery. This research is a Classroom Action Research conducted in two cycles, each cycle consists of 4 stages namely planning, action, observation and reflection with the research process: (1) Learning by using the demonstration method (2) planning the form of classroom action in cycle II based on the results of the redleksi in cycle I. The subjects of this study were students of class VIII.a SMP Negeri 10 Mandau in the 2023/2024 school year totaling 32 students. Student learning outcomes show an increase in learning outcomes. In cycle I there were 2 students who were not complete in cycle II all students had 100% completeness. Therefore, the teacher in deepening students' speaking should use the demonstration learning model.